Sodium lactate infusion during a cycling time-trial does not increase lactate concentration or decrease performance - Ellis, D.; Simmons, C.; Miller, B. F. (European Journal of Sport Science, 2009)
The aim of this study was to determine whether an exogenous sodium lactate infusion increases blood lactate concentration and decreases performance during a 20-km time-trial. Highly trained male cyclists performed a 20-km time-trial with a saline (control) or sodium lactate infusion. Sodium lactate was infused at rates previously observed to raise blood lactate concentration by 2 mmol·l-1 in trained individuals cycling at 65% of maximum oxygen uptake. Blood lactate concentration increased (P=0.0001) during both the control and sodium lactate trials compared with rest, with peak values of 9.6 and 10.6 mmol·l-1, respectively. The increase in sodium lactate over time was not significantly different from the control (P=0.34). Time to complete the time-trial and average power for the time-trial were not significantly different between the control (25.72±0.80 min; 348.0±32.4 W) and sodium lactate trials (25.58±0.93 min; 352.6±39.3 W). In addition, rating of perceived exertion, heart rate, and respiratory parameters did not differ between trials. In conclusion, when exogenous lactate is infused during a 20-km cycling time-trial, an exercise bout performed above the maximal lactate steady state, blood lactate concentration did not increase. Furthermore, exogenous lactate infusion did not decrease exercise performance, increase perceived exertion, or change respiratory parameters. Because lactate per se did not change performance outcomes or measured perceived exertion, we suggest that alternative objective measures of exercise intensity and performance be explored.